Citizens in the Graeco-Roman world : aspects of citizenship from the archaic period to AD 212 - Cecchet, Lucia; Busetto, Anna (Leiden : Brill, 2017)
The volume provides a collection of studies on citizenship in the Graeco-Roman world and the political and philosophical reflection on it. It encourages the reader to complement the traditional institutional approach to citizenship with a broader perspective. The twelve studies contained in this volume discuss some key-aspects of citizenship from its emergence in Archaic Greece until the Roman period before AD 212, when Roman citizenship was extended to all the free inhabitants of the Empire. The book explores the processes of formation and re-formation of citizen bodies, the integration of foreigners, the question of multiple-citizenship holders and the political and philosophical thought on ancient citizenship. The aim is that of offering a multidisciplinary approach to the subject, ranging from literature to history and philosophy, as well as encouraging the reader to integrate the traditional institutional and legalistic approach to citizenship with a broader perspective, which encompasses aspects such as identity formation, performative aspect and discourse of citizenship.
Looking for citizenship in archaic Greece : Methodological and historical problems / Maurizio Giangiulio -- Re-shaping and re-founding citizen bodies: the case of Athens, Cyrene and Camarina / Lucia Cecchet -- Politeia in Greek federal states / Chiara Lasagni -- The case of multiple citizenship holders in the Graeco-Roman east / Andreea Ştefan -- Citizens among outsiders in Plautus's Roman cosmopolis : A moment of change / Elena Isayev -- Were children second-class citizens in Roman society? Information technology resources for a new vision of an ancient issue / Donato Fasolini -- Egyptians and citizenship from the first century AD to the Constitutio Antoniniana / Valerio Marotta -- Fifty years before the Antonine constitution: access to Roman citizenship and exclusive rights / Arnaud Besson -- Metaphorical appeals to civic ethos in Lycurgus' Against Leocrates / Jakub Filonik -- Alteram loci patriam, alteram iuris: "double fatherlands" and the role of Italy in Cicero's political discourse / Filippo Carlà-Uhink -- Ancient and modern sources of Hegel's conception of the Roman citizenship / Valerio Rocco Lozano -- The idea of cosmopolitanism from its origins to the 21st century / Anna Busetto
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: občanství -- starověké Řecko; občanství -- starověký Řím; citizenship -- ancient Greece; citizenship -- ancient Rome; sborníky konferencí; e-knihy online; proceedings of conferences; e-books online